2011
DOI: 10.1186/1472-6920-11-18
|View full text |Cite
|
Sign up to set email alerts
|

Teaching tools in Evidence Based Practice: evaluation of reusable learning objects (RLOs) for learning about Meta-analysis

Abstract: BackgroundAll healthcare students are taught the principles of evidence based practice on their courses. The ability to understand the procedures used in systematically reviewing evidence reported in studies, such as meta-analysis, are an important element of evidence based practice. Meta-analysis is a difficult statistical concept for healthcare students to understand yet it is an important technique used in systematic reviews to pool data from studies to look at combined effectiveness of treatments. In other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Additionally, although MA has been included in most evidence-based practice modules in nursing curricula, many students fail to completely understand MA statistical techniques or the various important concepts that underpin. 34 This study found that 57 out of 74 (∼77%) SRs did not include any meta-analyses, which may have originated from the extremely limited technique to pool data from individual studies. Another possibility is that some topics struggle to synthesise quantitative evidence, such as the review of qualitative studies.…”
Section: Discussionmentioning
confidence: 82%
“…Additionally, although MA has been included in most evidence-based practice modules in nursing curricula, many students fail to completely understand MA statistical techniques or the various important concepts that underpin. 34 This study found that 57 out of 74 (∼77%) SRs did not include any meta-analyses, which may have originated from the extremely limited technique to pool data from individual studies. Another possibility is that some topics struggle to synthesise quantitative evidence, such as the review of qualitative studies.…”
Section: Discussionmentioning
confidence: 82%
“…Intuitively, if copious records are retrieved from database, more time is expected for study selection and data extraction; therefore, the number of records retrieved may relate to the time taken for publication. Furthermore, performing meta-analysis requires specific training but it has been reported that many nursing researchers and students did not fully understand the statistical techniques of meta-analysis or the various important concepts that underpin it [ 9 ]. Thus, the inclusion of meta-analyses in the SR may take more time to complete the review.…”
Section: Introductionmentioning
confidence: 99%
“…It is often used in systematic reviews and is increasingly a method and topic that appears in student dissertations. There are many courses and resources for meta-analysis available online, such as: the Cochrane open learning materials; two ESRC RDI courses a ; Michael Borenstein’s course on Statistics.com b ; reusable learning objects [1] c ; and the EPPI-Centre’s MSc module on synthesis d . This paper, and the software it describes, is a contribution to these resources; aiming to support the teaching of meta-analysis and its use in student learning.…”
Section: Resultsmentioning
confidence: 99%